2020
DOI: 10.1038/s41419-020-2448-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: ERK1/2-Nanog signaling pathway enhances CD44(+) cancer stem-like cell phenotypes and epithelial-to-mesenchymal transition in head and neck squamous cell carcinomas

Abstract: Head and neck squamous cell carcinomas (HNSCCs) harbor a subset of cells that are CD44(+) and present with malignancy and radiotherapy resistance. As a key regulator of self-renewal, Nanog expression not only determines cell fate in pluripotent cells but also mediates tumorigenesis in cancer cells; thus, we examined the role of Nanog in CD44 (+) HNSCC. Three HNSCC cell lines, tumor xenografts, and patient tumors were examined. Nanog levels were significantly higher in CD44(+) HNSCC spheroids than in CD44(−) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Thus, the crested duck can form a protective tissue on fragile crested tissue. NANOG, which is involved in the development of neural crest stem cells, has been shown to play a role in the pathogenesis of many cancers by regulating cell proliferation, invasion, and metastasis [36,37]. Therefore, we suggest that NANOG could be a key gene in DNA damage repair and the GCR in CC ducks.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, the crested duck can form a protective tissue on fragile crested tissue. NANOG, which is involved in the development of neural crest stem cells, has been shown to play a role in the pathogenesis of many cancers by regulating cell proliferation, invasion, and metastasis [36,37]. Therefore, we suggest that NANOG could be a key gene in DNA damage repair and the GCR in CC ducks.…”
Section: Discussionmentioning
confidence: 85%
“…4 ). Similarly, Yin et al reported that co-expression of OCT4 and NANOG induced development of CSC characteristics and enhanced EMT in hepatocellular carcinoma, and Huang et al showed that ERK-NANOG signaling promoted CSC phenotypes and EMT in HNSCC 36 , 37 .…”
Section: Discussionmentioning
confidence: 97%
“…29,37,38 CD44 has been reported to interact with Nanog through ERK1/2 and β-catenin pathways. 39,40 These candidate drugs for CSCs could not suppress stemness potential, at least in esophageal cancer. Here, it is appropriate to discuss stemness suppression by iron chelators.…”
Section: Discussionmentioning
confidence: 99%